All about … schematic learning. Issue 3 (4th February 2019) - May, Rachel; Stevenson, Sarah; McGachy, Nicky; Bloch, Carole; Louis, Stella
Abstract : Understanding children's schemas, or 'patterns of behaviour and thinking', enables practitioners to support them as they use them to deepen their learning, explain Professor Tina Bruce CBE, Dr Stella Louis and Dr Carole Bloch